Suppose 46*m = 49*m - 18. Solve 9*p = m*p + 6 for p.

2

Let a(p) = -p - 4. Let z be a(-5). Suppose 0 = 9*w - 5*w - 56. Let n = 16 - w. Solve -3 - z = n*t for t.

-2

Let l = -22 + 14. Let x(z) be the second derivative of z520 + 2*z43 - z36 - 5*z22 + 3*z. Let t be x(l). Solve -t*i = -0 - 6 for i.

2

Let g = -56 + 62. Solve -g*a - 9 = -3*a for a.

-3

Suppose 0 = -b - 0*b - 17. Let q = -9 - b. Solve -3*k + q*k = -5 for k.

-1

Let k(d) = 17 - 3 - 2 - d. Let i be k(10). Solve i*x + 4 = -2*x for x.

-1

Suppose -5*t + 31 = -6*t. Let g = 43 + t. Solve g = 5*a - 13 for a.

5

Let r(p) = 3*p + 50. Let x be r(-15). Suppose 4*g = 5*z + 95, -2*g - z + 2*z + 55 = 0. Solve 5*w + x = g for w.

5

Let x = -1 + 11. Let h(t) = -2*t**2 + 16*t + 4. Let d be h(11). Let c be d/(-10) - 210. Solve -l + c*l + x = 0 for l.

-2

Let x® = -3 - 5*r - 2*r + r. Let c(v) = v + 1. Let a(i) = 4*c(i) + x(i). Let w be a(-1). Solve w*z - 11 = 4 for z.

5